2015
DOI: 10.1080/17513758.2015.1027309
|View full text |Cite
|
Sign up to set email alerts
|

Allee effects and population spread in patchy landscapes

Abstract: Invasion of alien species is one of the major threats for natural community structures, potentially leading to high economic and environmental costs. In this work, we study through a reaction-diffusion model the dynamics of an invasion in a heterogeneous environment and in the presence of a strong Allee effect. We model space as an infinite landscape consisting of periodically alternating favourable and unfavourable patches. In addition, we consider that at the interface between patch types individuals may sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 32 publications
1
36
0
Order By: Relevance
“…Theoretical studies have showed that a high enough clustering level could actually pin the invasion front if the invader suffers from Allee effects, even if the difference between the rich and the poor patches is small (Dowdall et al 2017). Besides, invasions can also be pinned for lower clustering levels for greater heterogeneity between the patches (Maciel and Lutscher 2015), suggesting that invasion pinning depends on the interaction between the two parameters. Other theoretical studies suggest that the effect we demonstrated on one-dimensional theoretical and laboratory landscapes should persist in higher dimensional spaces (With andKing 1999, Roques andChekroun 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Theoretical studies have showed that a high enough clustering level could actually pin the invasion front if the invader suffers from Allee effects, even if the difference between the rich and the poor patches is small (Dowdall et al 2017). Besides, invasions can also be pinned for lower clustering levels for greater heterogeneity between the patches (Maciel and Lutscher 2015), suggesting that invasion pinning depends on the interaction between the two parameters. Other theoretical studies suggest that the effect we demonstrated on one-dimensional theoretical and laboratory landscapes should persist in higher dimensional spaces (With andKing 1999, Roques andChekroun 2010).…”
Section: Discussionmentioning
confidence: 99%
“…A possible next step would be to explore other individual fitness metrics such as reproductive output (e.g., the number of eggs carried by females), or to experimentally assess inbreeding depression. Beyond these fitness considerations, limitations in population growth rates can be linked to Allee effects (Maciel & Lutscher, 2015;Taylor & Hastings, 2005), but in our study case, this hypothesis is unlikely because crayfish abundances have been high in many ponds in the recent past (Table S5).…”
Section: Ecological and Evolutionary Consequences Of Genetic Drift mentioning
confidence: 94%
“…If one uses a reaction-diffusion model to describe the spatiotemporal evolution of a single species that is subject to the strong Allee effect, a typical reaction function is the so-called bistable nonlinearity. Indeed, the role of Allee effect in population spreading and invasion in reaction-diffusion or integro-differential models has been explored in many research works; see [19,27,28,31,36,44,45,47,48,49,51] to mention a few. Now, let us assume that the species lives in an entire line habitat R =: (−∞, ∞) and distributes only within a bounded interval initially.…”
mentioning
confidence: 99%